Delay constrained distributed multicast routing algorithm. - Im, Yongjun
We propose a delay constrained multicast algorithm that finds a multicast tree between one source node and multiple destination nodes in communication networks. The proposed algorithm, which provides multicasting and guaranteed QoS (Quality of Service) services at the network layer, is also designed to find a reduced cost routing tree. We present a distributed algorithm by which the routing tree is computed through a single round of message exchange between network nodes, consequently reducing the number of messages and the accompanying computation time. The proposed algorithm is verified by simulation and it is shown that it exhibits superior performance compared to existing algorithms.
Keywords: Multicast; Distributed algorithm; Routing